PENGARUH CITRA MEREK DAN KEPERYAAN MEREK TERHADAP LOYALITAS PELANGGAN AQUA GALON PADA AQUA HOME SERVICE FISKA KOTA BANDUNG - Destiko Rahmadani Pamungkas; Evi Sofiati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines the influence of brand image and brand trust on customer loyalty of AQUA gallon products at AQUA Home Service (AHS) Fiska, Bandung City. The research is motivated by the decline in AQUA gallon sales by 12.76% from January to November 2025, while competing brands experienced significant growth. A quantitative verificative approach was employed using a survey method. The sample consisted of 109 active customers selected through purposive sampling. Data were collected using Likert-scale questionnaires and analyzed through multiple linear regression supported by classical assumption tests, t-test, F-test, and coefficient of determination. The findings reveal that brand image and brand trust have a positive and significant effect on customer loyalty, both partially and simultaneously. Brand trust shows a more dominant influence compared to brand image. These results highlight that customer loyalty in the bottled drinking water distribution sector is strongly influenced by customers’ confidence in product consistency and brand credibility. The study provides managerial implications for strengthening long-term customer loyalty through trust-based marketing strategies.